2000
DOI: 10.1161/01.hyp.35.1.280
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-Mediated Calcium Signaling in Preglomerular Smooth Muscle Cells

Abstract: Abstract-This study was performed to test the hypothesis that endothelin peptides differentially influence intracellular calcium concentration ([Ca 2ϩ ] i ) in preglomerular microvascular smooth muscle cells (MVSMC), in part through activation of endothelin (ET) A receptors. Experiments were performed in vitro with the use of single MVSMC freshly isolated from rat preglomerular microvessels. The effect of ET-1, ET-2, and ET-3 on [Ca 2ϩ ] i was measured with the use of the calcium-sensitive dye, fura 2, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 36 publications
4
43
0
Order By: Relevance
“…The [Ca 2+ ]i response of shark anterior mesenteric artery VSM to ETBR stimulation in Ca 2+ -free Ringer was characterized by a prolonged peak of approximately 100·s. This contrasts with the short duration spike (<25·s) typical of the responses seen in mammalian VSM (Schroeder et al, 2000). The current studies were performed intentionally at 20-21°C, because shark cells are accustomed to ambient temperatures of 13-17°C in the sea, and our experience is that they lose viability at temperatures above 25°C.…”
Section: Discussionmentioning
confidence: 95%
“…The [Ca 2+ ]i response of shark anterior mesenteric artery VSM to ETBR stimulation in Ca 2+ -free Ringer was characterized by a prolonged peak of approximately 100·s. This contrasts with the short duration spike (<25·s) typical of the responses seen in mammalian VSM (Schroeder et al, 2000). The current studies were performed intentionally at 20-21°C, because shark cells are accustomed to ambient temperatures of 13-17°C in the sea, and our experience is that they lose viability at temperatures above 25°C.…”
Section: Discussionmentioning
confidence: 95%
“…A major product of the CYP450 hydroxylase pathway is the endogenous renal microvascular vasoconstrictor metabolite 20-HETE. 26 30 In addition, the peak responses to ET-1 are generated primarily by mobilization of Ca 2ϩ from intracellular stores, and the sustained elevations in [Ca 2ϩ ] i are the result of calcium influx. 30 CYP450 hydroxylase inhibition significantly attenuated the peak response at the lower doses and at higher doses of ET-1 diminished the sustained [Ca 2ϩ ] i phase, which supports the concept that 20-HETE produced by the vascular smooth muscle cell contributes to ET-1-evoked preglomerular vasoconstriction.…”
Section: Discussionmentioning
confidence: 99%
“…Also, ET-1, -2 and -3 could induce vascular contraction via activation of VSM ET B2 receptors [64]. For example, both ET A and ET B receptors are present and produce vasoconstriction in the renal circulation [65]. Also, studies using selective ET receptor agonists and antagonists have suggested the presence of the constrictor ET B receptors in human subcutaneous and rat mesenteric arteries, albeit in low numbers.…”
Section: Functions Of Et/et Receptorsmentioning
confidence: 99%
“…Vascular contraction to ET-1 is increased in rat hearts during ischemia/ reperfusion and in the rat pulmonary circulation in pulmonary hypertension [46]. Evidence indicates that a defect in VSM regulation of intracellular Ca 2+ may play a role in the augmented vascular reactivity to ET-1 in some forms of experimental hypertension [65,79]. However, vascular contraction to ET is unchanged in the aorta of SHR and is even decreased in the mesenteric arteries of DOCA-salt hypertensive rats [46,64].…”
Section: Vascular Response To Et In Hypertensionmentioning
confidence: 99%